The 2nd Indonesiaan Tobacco Control Research Dissemination Conference and Capacity Building Program - Lembaga Pengembangan Pendidikan, Penelitian dan Pengabdian Masyarakat Universitas Muhammadiyah Yogya (Lembaga Pengembangan Pendidikan, Penelitian dan, 2015)
KARYA TULIS INI BERISI PROCEEDING DENGAN JUDUL : MAPPING THE INDONESIAN GOVERNMENT'S POSITION IN THE DECISION-MAKING PROCESS OF WORLD HEALTH ORGANIZATION FRAMEWORK CONVENTION ON TOBACCO CONTROL (WHO FCTC) RATIFICATION, HARMONIZING THE INTERNATIONAL TRADE POLICIES AND THE RIGHT FOR HEALTH PROTECTION MEASURES: CASE STUDY ON WHO DSB RULING ON US-CLOVE CIGARETTES, CONTENT ANALYSIS OF CIGARETTE ADVERTISEMENT IN NEWSPAPER „KEDAULATAN RAKYAT‟ (1990-2013), THE ECONOMIC BURDEN OF SMOKING-ATTRIBUTABLE DISEASES TO THE GOVERNMENT HEALTHCARE EXPENDITURES IN TOLITOLI DISTRICT 2014, WARRANTIES AND CERTAINTY OF LEGAL PROTECTION OF CHILDREN FROM CIGARETTE ADDICTION ON 113 SMOKE FREE AREA POLICIES IN INDONESIA, ANALYSING CIGARETTE CONTROL POLICY INITIATION THROUGH SURVEY ON PUBLIC OPINION CASE STUDY IN MALANG AND BATU CITIES, MONITORING EVALUATION FOR IMPLEMENTATION REGIONAL REGULATION NO 5 YEAR 2008 ABOVE SMOKE- FREE AREA (SFA) AND SMOKE- RESTRICTED AREA (SRA) TO PUBLIC PLACE IN SURABAYA, THE EFFECT OF HOME CIGARETTE SMOKE EXPOSURE TO THE RESPIRATORY DISEASES AMONG UNDERFIVES IN DENPASAR, MONITORING AND EVALUATION OF PICTORIAL HEALTH WARNINGSS ON CIGARETTES‟ ADVERTISEMENTS BASED ON INDONESIA GOVERNMENT REGULATION PP NO. 109/ 2012, THE ECONOMIC IMPACT OF SMOKING AMONG INDONESIAN POPULATION: PREMATURE MORTALITY COSTS AND YEARS OF POTENTIAL LIFE LOST (YPLL) STUDY